OFFSET
0,3
COMMENTS
FORMULA
G.f.: G(t,z) = 1 - (1-C-z*C)/(1-z+t*z-t*z*C), where C=C(t,z) is given by t*z^2*C^2 - (1-2*z^2+2*t*z^2)*C + 1-z^2+t*z^2 = 0.
EXAMPLE
T(5,1)=3 because we have U(DUU)D, U(DUU)U, and UU(DUU), where U=(1,1) and D=(1,-1) (the DUU's are shown between parentheses).
Triangle starts:
1;
1;
2;
3;
5, 1;
7, 3;
11, 9;
15, 19, 1;
23, 42, 5;
MAPLE
eq := t*z^2*C^2-(1-2*z^2+2*t*z^2)*C+1-z^2+t*z^2 = 0: C := RootOf(eq, C): G := 1-(1-C-z*C)/(1-z+t*z-t*z*C): Gser := simplify(series(G, z = 0, 23)): for n from 0 to 18 do P[n] := sort(coeff(Gser, z, n)) end do: 1; for n to 18 do seq(coeff(P[n], t, k), k = 0 .. ceil((1/3)*n)-1) end do; # yields sequence in triangular form
CROSSREFS
KEYWORD
nonn,tabf
AUTHOR
Emeric Deutsch, Jun 18 2011
STATUS
approved